Theoretical Study on Methods to Increase the Efficiency and Performance of Solar Air Heater - Nagrath, Vishwas; Haq, Seyed Hunzela; Mishra, Harshit; Wazeer, Adil (Asian Review of Mechanical Engineering, 2020)
Due to the low thermal performance of solar air heater, different methodologies are adopted to increase its performance namely fins, artificial roughness etc. Thermal performance is obtained for different values of Reynolds number, emissivity of a plate, tilt angle and by employing different kinds of artificial roughness. There are numerous techniques which can be used on the absorber plate to increase the efficiency and Thermo-hydraulic performance of the solar air heater. We can use single roughness geometry or can combine two different roughness geometries also to get best output. By defining different correlations of heat transfer and friction factor in roughened ducts of solar air heater, we can get the best artificial roughness that can be utilized in the solar air heater. By selecting the coating material, we can improve the performance of solar air heater. As we must use our energy for future purpose, we have to store it and for that thermal energy storage materials are used. This is also one of the techniques to increase the effectiveness of solar air heater. In this article, focus has been given on study of methods of increasing the performance of solar air heater such as providing artificial roughness, increasing the collector aspect ratio etc.